"News you don't believe": audience perspectives on fake news - Nielsen, R; Graves, L (Reuters Institute for the Study of Jounalism, 2017)
In this RISJ Factsheet by Rasmus Kleis Nielsen and Lucas Graves, we analyse data from 8 focus groups and a survey of online news users to understand audience perspectives on fake news. On the basis of focus group discussions and survey data from the first half of 2017 from the United States, the United Kingdom, Spain, and Finland, we find that: People see the difference between 'fake news' and news as one of degree rather than a clear distinction; When asked to provide examples of 'fake news', people identify poor journalism, propaganda (including both lying politicians and hyperpartisan content), and some kinds of advertising more frequently than false information designed to masquerade as news reports; 'Fake news' is experienced as a problem driven by a combination of some news media who publish it, some politicians who contribute to it, and some platforms that help distribute it; People are aware of the 'fake news' discussion and see “fake news” in part as a politicized buzzword used by politicians and others to criticize news media and platform companies; The 'fake news' discussion plays out against a backdrop of low trust in news media, politicians, and platforms alike—a generalized scepticism toward most of the actors that dominate the contemporary information environment; Most people identify individual news media that they consider consistently reliable sources and would turn to for verified information, but they disagree as to which and very few sources are seen as reliable by all. Our findings suggest that, from an audience perspective, 'fake news' is only in part about fabricated news reports narrowly defined, and much more about a wider discontent with the information landscape – including news media and politicians as well as platform companies. Tackling false news narrowly speaking is important, but it will not address the broader issue that people feel much of the information they come across, especially online, consists of poor journalism, political propaganda, or misleading forms of advertising and sponsored content.